GASTRIC MALT LYMPHOMA – CURRENT DIAGNOSTIC AND THERAPEUTIC STRATEGIES - Jonatan Rataj; Kamil Harenza; Karolina Ollik; Marlena Radzka; Michalina Kosowska; Justyna Jankowska; Adrianna Wiekiera; Mateusz Wiekiera (International Journal of Innovative Technologies in Social Science, 2025)
Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is a distinct subtype of extranodal marginal zone B-cell lymphoma strongly associated with Helicobacter pylori infection. This review presents an overview of current diagnostic and therapeutic strategies, highlighting recent developments in molecular diagnostics and evidence-based management. The diagnosis relies on histopathological evaluation supported by immunohistochemistry and molecular testing for characteristic translocations, particularly t(11;18)(q21;q21). First-line therapy remains H. pylori eradication, which induces complete and durable remission in most patients, including some who are H. pylori-negative. For those unresponsive to antibiotics, radiotherapy or rituximab-based immunotherapy achieves excellent local control and survival rates. Prognosis is generally favourable, with five-year overall survival exceeding 90%. However, complications such as gastrointestinal bleeding, perforation, and histologic transformation into diffuse large B-cell lymphoma (DLBCL) may occur. Early detection, accurate staging, and an individualized, risk-adapted therapeutic approach remain key factors influencing long-term outcomes. Advances in endoscopic imaging, molecular characterization, and targeted therapies continue to refine the management of gastric MALT lymphoma, supporting the trend toward more personalized treatment strategies and improved patient prognosis.